History and Drama The Pan-European Tradition - Küpper , Joachim; Mosch, Jan; Penskaya, Elena (De Gruyter, 2019)
Historiography and literature are verbal representations of actions and events that either have happened or could happen in the human lifeworld. As such, they possess an uncanny 'family resemblance' that has impelled theorists since Antiquity to define the limits of the two 'sister arts.' Historiographical texts, from one point of view, are liable to veer towards fiction.